ChemInform Abstract: Self‐Immolative Spacers: Kinetic Aspects, Structure—Property Relationships, and Applications. Issue 31 (August 2015) - Alouane, Ahmed; Labruere, Raphael; Le Saux, Thomas; Schmidt, Frederic; Jullien, Ludovic
Abstract Review: 150 refs.